Caribou consumption in northern Canadian communities. Issue 16 (1st September 2016) - Chiu, Angie; Goddard, Ellen; Parlee, Brenda
ABSTRACT: Chronic wasting disease (CWD) is a transmissible spongiform encephalopathy (TSE) found in both farmed and wild deer, elk, and moose in the United States and Canada. Surveillance efforts in North America identified the geographical distribution of the disease and mechanisms underlying distribution, although the possibility of transmission to other cervids, including caribou, and noncervids, including humans, is not well understood. Because of the documented importance of caribou ( Rangifer tarandus ) to human populations in the northern regions of Canada, a risk-management strategy for CWD requires an understanding of the extent of potential dietary exposure to CWD. Secondary 24-h dietary recalls conducted among Inuvialuit and Inuit in 4 communities in the Northwest Territories and Nunavut were employed in this study. Econometric demand systems were estimated to model the impacts of individual- and community-level socioeconomic characteristics on expenditures on caribou and other foods, in order to examine the households' ability to consume other foods in response to changing levels of caribou consumption. Thirty-five percent of respondents reported consuming caribou in the survey period, and caribou comprised, on average, 26% of daily dietary intake by weight, or approximately 65 g/d, across individuals in the 4 communities. Consuming caribou was also shown to exert positive impacts on dietary quality, as measured by calorie intake and dietary diversity. Communities with less access to employment, income and food stores are predicted to be constrained in their ability to obtain an adequate diet in the event of scarcity of caribou meat.